APLIKASI FORUM TRANSLASI BAHASA INDONESIA-MANADO BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING - Vivi Peggie Rantung; Abimanyu Marvie Dwisuprapto; Ferdinan Ivan Sangkop (Fakultas Ilmu Komputer, Universitas Klabat, 2024)
Manado language (Manadonese) is one of the languages that is registered in the ISO 639-3 standard system with the code of xmm and used by 3.320.000 users. In daily life, Manadonese is commonly used verbally. In its oral use, Manadonese becomes a low-resource language, meaning it lacks text-based resources, which makes it difficult to develop various linguistic-based technologies to preserve Manadonese. This research aimed to provide a data source to develop advanced linguistic-based technology. The methodology used for this research is extreme programming (XP). The result of this research is a Web-Based Application Of Indonesia-Manado Translation Forum with various functions, such as uploading Indonesian articles that will be translated into Manadonese, from this diverse amount of translation the best of it will be chosen to be processed every word and sentence that will be saved in the database. The application is tested with Acceptance Testing as an indicator and the result shows that the forum managed to accomplish the goal set up before.